Towards language justice: queering solidarities between interpreters, service providers, and community members - Touma, Mikhael; Hanman-Siegersma, Frankie; Ah Ket, Blossom; Matthews, Paige; Quijano de Brasdefer, Monica (Frontiers in Communication, 2025)
This article is a dialogue between community interpreters (Arabic and Spanish), service provider (narrative therapy practitioner), and a community member (Spanish-speaking) exploring the linguistic challenges that LGBTIQ+ Forcibly Displaced People (LFDP) experience during their settlement process in Australia. English language supremacy shapes the forms of epistemic and structural injustice that subjugate LFDP. In order to highlight the power invested in language services, the authors examine queer and feminist interpreting and translating practices which centre lived experience. This article proposes a practice of solidarity between the language practitioner (community interpreter), community member and service provider in the context of LFDP, which may be in tension with the AUSIT Code of Ethics’ principles of impartiality and neutrality. The authors suggest the need for community interpreters to engage in more meaningful allyship and solidarity with LFDP, their histories, and lived experiences in order to achieve best outcomes for the community.